Degeneration of Neuromuscular Junction in Age and Dystrophy - Rudolf, Rüdiger; Khan, Muzamil Majid; Labeit, Siegfried; Deschenes, Michael R. (Frontiers in Aging Neuroscience, 2014)
Functional denervation is a hallmark of aging sarcopenia as well as of muscular dystrophy. It is thought to be a major factor reducing skeletal muscle mass, particularly in the case of sarcopenia. Neuromuscular junctions serve as the interface between the nervous and skeletal muscular systems, and thus they may receive pathophysiological input of both pre- and postsynaptic origin. Consequently, neuromuscular junctions are good indicators of motor health on a systemic level. Indeed, upon sarcopenia and dystrophy, neuromuscular junctions morphologically deteriorate and exhibit altered characteristics of primary signaling molecules, such as nicotinic acetylcholine receptor and agrin. Since a remarkable reversibility of these changes can be observed by exercise, there is significant interest in understanding the molecular mechanisms underlying synaptic deterioration upon aging and dystrophy and how synapses are reset by the aforementioned treatments. Here, we review the literature that describes the phenomena observed at the neuromuscular junction in sarcopenic and dystrophic muscle as well as to how these alterations can be reversed and to what extent. In a second part, the current information about molecular machineries underlying these processes is reported.